Effect of Addition of Seaweed (Sargassum sp.) Charcoal with Pure Graphite on the Microstructure of Graphene Oxide Synthesized by the Modified Hummer’s Method - Gebby Wevi Angraini; Ramli (Department of Physics, Universitas Negeri Padang, 2023)
Graphite acts as a source of carbon which is used in the synthesis of graphene oxide. Graphite has a fairly high price, so there are limitations to the use of graphite on a large scale. Brown sea grass (Sargassum sp.) contains carbon and is not yet well exploited in Indonesia, so experiments can be done by mixing graphite and Sargassum sp. to minimize excessive use of graphite. The purpose of this study is to determine the addition of Sargassum sp. charcoal could affect the microstructure of graphene oxide synthesized using the modified Hummer method. Where a comparison of 5 variations of the composition of pure graphite and Sargassum sp. charcoal was carried out, namely (100:0; 70:30; 60:40; 50:50, and 0:100) %. The resulting graphene oxide was characterized by X-Ray Diffraction (XRD), Fourier Transform Infrared (FTIR), and Scanning Electron Microscope (SEM). It can be concluded that the addition of Sargassum sp. charcoal to pure graphite influences the microstructure of the graphene oxide. In the XRD test, an average crystal size of 24-33 nm with a cubic crystal structure was obtained; in the FTIR test, there was a bond between carbon (C), hydrogen (H), and oxygen (O); and in the SEM test, the average particle size was 1647–1887 nm. If 30% Sargassum sp. charcoal is added to 70% pure graphite, the larger the particle size. This causes the surface pores to become larger so that their properties as supercapacitors are better produced and have structures that tend to be like pieces.